Effects of Inoculation with Koji and Strain Exiguobacterium profundum FELA1 on the Taste, Flavor, and Bacterial Community of Rapidly Fermented Shrimp Paste - Huanming Liu; Ailian Huang; Jiawen Yi; Meiyan Luo; Guili Jiang; Jingjing Guan; Shucheng Liu; Chujin Deng; Donghui Luo (Foods, 2024)
This study was conducted to investigate the effect of inoculation with Exiguobacterium profundum FELA1 isolated from traditional shrimp paste and koji on the taste, flavor characteristics, and bacterial community of rapidly fermented shrimp paste. E-nose and e-tongue results showed higher levels of alcohols, aldehydes, and ketones, enhanced umami and richness, and reduced bitterness and astringency in samples of shrimp paste inoculated with fermentation (p < 0.05). Eighty-two volatile compounds were determined using headspace solid-phase microextraction and gas chromatography–mass spectrometry (HS-SPEM-GC-MS). The contents of 3-methyl-1-butanol, phenylethanol, isovaleraldehyde, and 2-nonanone in the inoculated samples were significantly increased (p < 0.05), resulting in pleasant odors such as almond, floral, and fruity. High-throughput sequencing results showed that the addition of koji and FELA1 changed the composition and abundance of bacteria and reduced the abundance of harmful bacteria. Spearman’s correlation coefficient indicated that the alcohols, aldehydes, and ketones of the inoculated fermented samples showed a strong correlation (|ρ| > 0.6) with Virgibacillus and Exiguobacterium, which contributed to the formation of good flavor in the fast fermented shrimp paste. This study may offer new insights into the production of rapidly fermented shrimp paste with better taste and flavor.